Of G-Men and Eggheads : The FBI and the New York Intellectuals - Rodden, John (Book collections on Project MUSE., 2017)
"During the Cold War, dissent against U.S. international policy was looked upon as inherently suspicious. No one was more suspicious than outspoken left-leaning intellectuals, especially those who lived in Manhattan. For national security reasons, the federal government expended considerable resources surveilling men and women who might harbor communist sympathies and exert influence over others. In this book, John Rodden reveals how the FBI and CIA kept track of three highly regarded New York intellectuals--Lionel Trilling, Dwight Macdonald, and Irving Howe"--